The effects of oral administration of curcumin–galactomannan complex on brain waves are consistent with brain penetration: a randomized, double-blinded, placebo-controlled pilot study. (3rd June 2022) - Khanna, Aman; Das S, Syam; Kannan, R.; Swick, Andrew G.; Matthewman, Cristina; Maliakel, Balu; Ittiyavirah, Sibi P.; Krishnakumar, I. M.
ABSTRACT: Overview: A novel highly bioavailable curcumin-galactomannan (CGM) formulation was shown to have improved blood-brain-barrier (BBB) permeability of free curcuminoids in animal models; however, this has not been established in humans. The present study was conducted to determine the functional effects of CGM on brain waves in healthy individuals, owing to its BBB permeability. Methods: A total of 18 healthy volunteers aged 35–65 were randomly assigned to consume 500 mg CGM, Unformulated curcumin (UC) or Placebo capsules twice daily for 30 days. Electroencephalogram (EEG) measurements, audio-visual reaction time tests and a working memory test were conducted at baseline and after 30 days. Results: Supplementation of CGM resulted in a significant increase in α- and β-waves ( p < 0.05) as well as a significant reduction in α / β ratio in comparison with unformulated curcumin and placebo groups. Furthermore, the CGM showed significant reduction in the audio-reaction time (29.8 %; p < 0.05) in comparison with placebo and 24.6% ( p < 0.05) with unformulated curcumin. The choice-based visual-reaction time was also significantly decreased (36%) in CGM as compared to unformulated curcumin and placebo which produced 15.36% and 5.2% respectively. Conclusion: The observed increase in α and β waves and reduction in α / β ratio in the CGM group suggest that CGM can influence the brain waves in healthy subjects in a manner consistent with penetration of the blood-brain-barrier. The EEG results correlated with improved audio-visual and working memory tests which further support the role of CGM on memory improvements and fatigue reduction.